Conception, integration, and experiences of information literacy through resource-based learning / Halida Yu - Halida, Yu (2014)

(untitled)
This study employed a case study qualitative inquiry to understand how teachers incorporated, and students experienced information literacy through a resource-based school project. Although project-based learning is claimed to promote information literacy development, most of the studies are conducted in the western society. Few studies have explored on this area in the context of developing nations to validate the findings. Employing the situated information literacy (SIL) theory, this study argues that learning could only be understood by observing the process within its context. It uses the three directions: SIL model to examine information literacy experiences from three directions, namely: actions and product, cognition, and participation directions. The participants in the study were four project teachers and twenty-three students (formed into four groups). They came from four schools that represent the “typical” schools in Malaysia. It adopted multiple data collection techniques: (a) teacher interview; (b) students focus-group interview (FGI); (c) students research journal. Two auxiliary techniques; classroom observation and students project report were also employed to triangulate the findings. The multiple method and data sources investigation have led to the multi-stage, simultaneous data collection research protocol research design to overcome time constraint and ethical challenges. Data were collected in three stages: (a) stage one: classroom observation, student journal; (b) stage two: teacher interview, collecting students’ journals, students FGI one; (c) stage three: students FGI two, collecting students’ report, FGI three. iv The findings revealed low information literacy awareness among all participants. Most teachers and students did not know, or have never heard about “information literacy”. Students’ competencies were found to be at the lower end of the information literacy model orders. Teachers and students were nevertheless, found to engage in some information-related activities, particularly on information seeking, information use and referencing, and report writing. Teachers’ teaching approaches were examined to understand knowledge transfer pertaining to research and writing skills. The results revealed that teachers did not play crucial role to demonstrate complex skills in these areas. Accordingly, students demonstrated low competencies in these skills. The straightforward nature of the project task and teacher’s teaching approach did not help to get students engaged into more challenging, informationbased activities. They were spared from engaging in critical thinking activities such as defining the task or the problem statement. They opted for convenience, rather than reliable information during the information seeking stage and relied mostly on internet resources. They were innocently unaware of ethical information use practices and plagiarised indiscriminately, and report writing, to some extent was about transporting chunks of information into their report. There was almost no reflection made on learning process and the end product. Despite the negative findings, students reported to have learned and benefited much from the project, some of which were, developing; ICT skills, information seeking skills, referencing skills, collaborative skills, and report writing skills. The study therefore, validates the argument against merely focusing on getting students to accomplish several v isolated skills in a decontextualized environment. It maintains that each learning experience should be understood within its context.